FIGURE 25 in Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata) - Grischenko, Andrei V.; Gordon, Dennis P.; Taylor, Paul D.; Kuklinski, Piotr; Denisenko, Nina V.; Spencer-Jones, Mary E.; Ostrovsky, Andrew N. (Zenodo, 2022)
FIGURE 25. Ancestrulae with periancestrular zooids in colonies of three Rhamphostomella species. A. R. scabra, A.V. Grischenko Collection (western Kamchatka shelf, Sea of Okhotsk). B. R. sibirica, P. Kuklinski Collection (Beringian coastal waters of Amchitka Island, Rat Islands, western Aleutian Islands). C. R. spinigera, Paralectotype, NHMW 92536 (Jan Mayen), initial part of colony. Scale bars: 250 μm. Published as part of Grischenko, Andrei V., Gordon, Dennis P., Taylor, Paul D., Kuklinski, Piotr, Denisenko, Nina V., Spencer-Jones, Mary E. & Ostrovsky, Andrew N., 2022, Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata), pp. 1-115 in Zootaxa 5131 (1) on page 81, DOI:10.11646/zootaxa.5131.1.1, http://zenodo.org/record/6521113